America's forgotten terrorists: the rise and fall of the Galleanists - Simon, Jeffrey D. (Potomac Books, an imprint of the University of Nebraska Press, 2022)
Introduction -- The Soul of the Movement -- Green Mountain Boys-Anarchist Style -- Targeting the Galleanists -- You Have Shown No Pity to Us! -- Roundup -- Final Blow -- The Legacy of the Galleanists -- Back Home Again.